Components and Scope of Artistic Literacy in Learning The Tempurung Dance Conceived By Artists (Catharsis, 2022)
This study discusses the components and scope of artistic literacy in dance learning initiated by artists, the problem found in this research is the lack of students' understanding of artistic literacy with the presence of Artists Entering Schools can help increase knowledge of art literacy in Tempurung dance learning. The purpose of this study is to analyze the components and scope of artistic literacy in Tempurung dance learning initiated by artists. This study used a qualitative method with interdisciplinary studies of arts education and arts sociology, a case study research design regarding groups with the Artist Entering School program for a certain period, the research location was at SMP Negeri 14 Pontianak, data and data sources were divided into two, namely primary data and secondary data. secondary. secondary, using observation techniques, interview techniques, and documentation techniques, data analysis techniques using interactive models, results and discussion 1) Art Literacy has a very important role in learning Tempurung dance to increase love and inheritance for students 2) Learning Tempurung Dance becomes a means material objects in this study 3) Artists Enter School Artists give dance lessons to students so that they become good platforms for schools and arts and culture teachers.